Desarrollo de competencias afectivas y su relación con el rendimiento escolar en los niños/as de 5 años de la I.E.I N°288 Ana Sofía Guillena Arana - Sinti Zalazar, Llyara Cristhina (2012)
The present work of lnvestigation developed with the aim to determine the relation that exists between the Affective Competitions and the School Performance of the 5-year-old children of the Educational lnitial lnstitution N o 288 "Ana Sofía Guillena Arana"- city of Rioja in the year 2011. For which the work of investigation belongs to the Basic type, level of investigation descriptive correlaciona! and his design of the investigation belongs to the design transeccional. One worked with a sample of 44 children and 44 parents. By means of the technology of the survey; there was gathered information of the Development of Affective Competitions; 2 classrooms were focused; those of the Rabits and that of the Chicks. To have information about the School Performance of the children and girls, about his achievements of learning, in the subjects of Mathematics, Communication, Science and Environment and Social Personnel, one resorted to the Record Consolidated of 2011 In synthesis, accused and analyzed the information and results, steadies himself that the children and girls possess a development of affective high-level competitions, opposite to an achievement of school performance in achievement foreseen (school quantitative notes of 15 - 20). In addition the alternate hypothesis is accepted by a confidence of 95 %, the same one that is . demonstrated in the linear graph and in the value that there has obtained of the coefficient of Spearman's correlation ( r s = O, 6642 ), which indicates and there is demonstrated that the School Performance is influenced positively in 44,12 % by the development of Affective Competitions. This wants to say that the level of development of Affective Competitions is related to the level of School Performance of the children and five-year-old girls of age of the Educational lnitial lnstitution N o 288 ''Ana Sofía Guil!ena Arana" of the city of Rioja, 2011.